2022
DOI: 10.3390/su141811528
|View full text |Cite
|
Sign up to set email alerts
|

The Procurement Agenda for the Transition to a Circular Economy

Abstract: The circular economy (CE) has emerged as an upcoming promising solution to global sustainability. Some policymakers have issued legislations to encourage the adoption of CE, and academics have published studies addressing CE from different approaches. However, adopting CE entails a disruptive shift from a linear economy to a closed-loop economy, where economic growth is decoupled from consumption growth. Though it is difficult to develop a uniform, structured approach for incorporating CE into procurement, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This insight resonates with the recent findings about the industry actors’ limited knowledge of the standard practices of CE within the construction sector (Adams et al , 2017; Benachio et al , 2020). Therefore, developing and institutionalising international standards to assess and certify the circularity of products and services has been suggested to accelerate the adoption of CE in procurement (Al-Sinan and Bubshait, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This insight resonates with the recent findings about the industry actors’ limited knowledge of the standard practices of CE within the construction sector (Adams et al , 2017; Benachio et al , 2020). Therefore, developing and institutionalising international standards to assess and certify the circularity of products and services has been suggested to accelerate the adoption of CE in procurement (Al-Sinan and Bubshait, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, procurement can play a vital role for CE implementation in the selection of suppliers and partners that adopt or have, for example, green certifications. Therefore, it has been suggested that procurement methods should include the CE implementation as a specific section that concentrates on the applicability of CE, defined criteria, checklists and rankings for suppliers that are working towards CE (Al-Sinan and Bubshait, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the Saudi measures to reduce emissions, several studies were reviewed to determine and discuss the commonly implemented measures [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Subsequently, a benchmark of the Saudi measures reported in the 2021 Nationally Determined Contribution (NDC) [20] was conducted against the common measures to reduce emissions.…”
Section: Methodsmentioning
confidence: 99%
“…Governments' common measures to reduce emissions include introducing policies (e.g., carbon pricing mechanisms, energy efficiency), supporting research and development, and deploying low-carbon technologies [6]. Governments can adopt one or more of the following policies to reduce GHG and carbon emissions in particular [7][8][9][10][11]:…”
Section: Policiesmentioning
confidence: 99%